2019
DOI: 10.1002/hyp.13579
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Function of a Mountain Fen at Low Elevation Under Dry Conditions

Abstract: Mountain fens are limited in their spatial extent but are vital ecosystems for biodiversity, habitat, and carbon and water cycling. Studies of fen hydrological function in northern regions indicate the timing and magnitude of runoff is variable, with atmospheric and environmental conditions playing key roles in runoff production. How the complex ecohydrological processes of mountain fens that govern water storage and release as well as peat accumulation will respond to a warmer and less snowy future climate is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 67 publications
1
31
0
Order By: Relevance
“…Several studies have examined the hydrologic function of wetlands and meadows in high mountain catchments (Chignell, Laituri, Young, & Evangelista, 2019; Chimner et al, 2019; Cooper et al, 2010, 2019; Lowry, Loheide, Moore, & Lundquist, 2011; Millar, Cooper, & Ronayne, 2018; Mosquera, Lazo, Célleri, Wilcox, & Crespo, 2015; Mosquera et al, 2016; Polk et al, 2017; Streich & Westbrook, 2019). Due to their excess of water and decreasing permeability with drying, wetlands can self‐regulate to keep the water table near the land surface (Rezanezhad et al, 2016).…”
Section: Mountain Aquifers and Flow Pathwaysmentioning
confidence: 99%
“…Several studies have examined the hydrologic function of wetlands and meadows in high mountain catchments (Chignell, Laituri, Young, & Evangelista, 2019; Chimner et al, 2019; Cooper et al, 2010, 2019; Lowry, Loheide, Moore, & Lundquist, 2011; Millar, Cooper, & Ronayne, 2018; Mosquera, Lazo, Célleri, Wilcox, & Crespo, 2015; Mosquera et al, 2016; Polk et al, 2017; Streich & Westbrook, 2019). Due to their excess of water and decreasing permeability with drying, wetlands can self‐regulate to keep the water table near the land surface (Rezanezhad et al, 2016).…”
Section: Mountain Aquifers and Flow Pathwaysmentioning
confidence: 99%
“…Bog frost tables were thinner and formed later than those in the fen (Figure 4; Ulanowski, 2014) and, combined with a lack of upgradient inflow, resulted in a faster decline in water tables (Figure 2b). Though not measured here, studies in other northern peatlands have shown a correlation between higher localized snow depth and thinner frost tables as well as delayed formation of ground ice (Moore, 1987; Streich & Westbrook, 2020). Frost tables were thinnest at this site in bog hollows (Figure 4), suggesting this may be an area of preferential snow accumulation.…”
Section: Discussionmentioning
confidence: 71%
“…These water table depths are comparable to those defined in other northern peatland‐dominated catchments. In a permafrost peatland system, bog‐to‐bog connectivity was associated with water table depths ~10 cm bgs (Connon et al, 2015), while in boreal fens active groundwater contribution to downgradient tributaries occurred at water tables between 5 and 10 cm bgs (Goodbrand et al, 2019), except for in extreme environments such as a montane fen underlain by well drained sediment, which contributed groundwater flow to water tables up to 90 cm bgs (Streich & Westbrook, 2020). It is likely that connectivity thresholds are landscape specific and defined by the local topography, peatland morphology and climate; the modelling of these systems would greatly aid in assessing the sensitivity of connectivity thresholds on system functioning in different environments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations